Implementasi Fungsi Manajemen pada Kegiatan Sertifikasi Pembimbing Manasik Haji - Novita Irawati; Asep Iwan Setiawan (Jurusan Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
This article aims to find out an implementasion of management function on the certification of the hajj pilgrims of the VII generation conducted by the hajj pilgrims of west java. The research used descriptive method with qualitative approach. The results showed on the hajj manasik guider certification program in the office of Religion Ministry West Java VII generation. There are managemen activity fungtions such as planning, organizing, mobilization and supervision that implemented well by meeting the standard procedure operational, this means that every process or stage contained in these activities has been implemented quite as well. Plans are done from the administrative stage of activities such as done from the design of activitiy budget, place, resource and material. The organizing organized well. The successful implementasion of management is seen from the implementation of the activity as well. In terms of supervision is done directedly by the team from the ministry of religious of West Java.